The indirect impact of road freight transport - case study: N3 Johannesburg to Durban road freight corridor - McKune, Andrew (Department of Civil Engineering, 2017)
South Africa's unique spatial challenges require more corridor transport relative to the size of the economy than most countries in the world. The overall aim of this investigation is to determine the estimated cost of the indirect impacts of road freight on the N3 corridor between Johannesburg and Durban. This corridor, approximately 600 kilometres in length, forms the link between the country's industrial hub (Johannesburg) and its key Port (Durban). The following research questions are posed: • What is the status quo of freight transport in a global, South African and Johannesburg to Durban Freight Corridor context? • What are the future growth forecasts for freight on the Johannesburg to Durban corridor? • What is the significance of freight transport in South Africa? • Does the reported total cost of road freight transport take into account a holistic approach when determining the costs? • How are direct and indirect impacts of road freight transport defined, and how do they differ? • What are the direct and indirect impacts of road freight transport? • What method can be used to assess the total indirect costs of all associated impacts? • What are the estimated costs of the indirect impacts of road freight transport on the Johannesburg to Durban Freight Corridor? • What are possible mitigation measures for the indirect impacts of road freight transport? • What will the estimated costs of the indirect impacts of road freight transport on the Johannesburg to Durban Freight Corridor be in over a 30-year horizon, when considering future projections and possible mitigation measures? • What are the alternative modes to road freight transport on the Johannesburg to Durban corridor?